Fungicide performance on Fusarium meridionale control, grain yield and grain damage in maize - Fingstag,Maiquiel Diego (2019)
ABSTRACT Gibberella ear rot (GER) in maize, caused by Fusarium graminearum species complex, is a destructive disease in southern Brazil and worldwide. Five field-experiments were conducted to determine fungicide efficacy, grain yield and grain quality (study I), as well as response of increasing rates (study II) on GER control, grain yield (GY) and grain damage (GD) in maize during the 2014/15 and 2015/16 growing seasons. Fungicides were sprayed 48 h before (preventive action) or 48 h after (curative action) inoculation of two Fusarium meridionale isolates (PR and MG). Study I consisted in applying nine active ingredients (metconazole, pyraclostrobin, tebuconazole, trifloxystrobin, prothioconazole, thiophanate-methyl, azoxystrobin, cyproconazole and carbendazim) present in eight commercial formulations at two sowing dates. Study II consisted in applying increasing rates of three fungicides evaluated at three sowing dates using only PR isolate. In study I, no differences were observed among fungicides when the variables GER, GY and GD were analyzed together. There were interactions between time of fungicide application and F. meridionale isolates when GER severity and GY were considered. Preventive fungicide application at different sowing dates and the use of MG isolate reduced GER by 11.6% and increased GY by 5.3%, compared to curative application. In study II, there was a significant interaction between fungicides and application time for GER, GY and GD. Preventive application of trifloxystrobin + prothioconazole (0.15 + 0.17 and 0.22 + 0.26 L ha-1), pyraclostrobin + metconazole (0.19 + 0.12 and 0.29 + 0.18 L ha-1) and carbendazim (2 L ha-1) reduced GER by 41 and 50%, 47 and 54%, and 54% at the three sowing dates, respectively. There was an increment of 45.7% and 46.8% in GY when trifloxystrobin + prothioconazole (0.15 + 0.17 and 0.22 + 0.26 L ha-1), respectively, were preventively sprayed at the three sowing dates, compared to the control treatment. Trifloxystrobin + prothiocanazole, pyraclostrobin + metconazole and carbendazim (1.0 and 2.0 L ha-1) preventively sprayed at two rates reduced GD incidence by 53.5 and 48.7%, 47.7 and 57.5%, 48.1 and 50.5%, respectively, for each fungicide and rate, and could be incorporated into a disease management program.